PERANCANGAN APLIKASI GAME 2D KILL GHOST MENGGUNAKAN UNITY - Robert Kristianus Gea; Immanuel H.G Manurung; Alexander F.K Sibero; Rianto Sitanggang (Jurnal Informatika Kaputama (JIK), 2023)
Game is one of the entertainment media that is in great demand by the community, from early childhood to adults. In general, games are divided into 7 (seven) types that are applied, namely, RTS (Real Time Strategy), FPS (First Person Shooter), RPG (Role Playing Game), Construction and Management Simulation Games, Vehicle Simulation, Action, Adventure and Fighting. Action games are a fighting game. This game was created using the C# programming language in the Unity game engine. In designing this game, the writer will implement an action game genre. The game has a two-dimensional appearance. Game testing is carried out using the blackbox method, as well as a user satisfaction survey. The test results show that the gameplay and features provided are interesting enough for an action game.